EFFECTIVENESS OF THE PRINCIPAL’S ROLE IN SUPERVISING THE IMPROVEMENT OF EDUCATIONAL QUALITY AT SDN SERANG 03 - Pratiwi, Ika; Andriani Sariwardani (Cakrawala Pedagogik, 2025)
Education necessitates comprehensive support from educators and education personnel to ensure the smooth progression of the learning process. Ensuring the quality of education is imperative to meet or exceed national education standards. Schools strive to provide high-quality learning services through the utilization of technology. The presence of professional, qualified, and competent teachers is an essential prerequisite. The implementation of educational supervision is expected to enhance the quality of education at the school level. This research employs a qualitative methodological approach, which examines natural phenomena in depth. The findings of qualitative research emphasize depth of understanding, rather than generalization. The research findings indicate that supervision is specifically aimed at developing and improving teacher professionalism, as well as facilitating their career development. The primary objective is to increase the effectiveness and productivity of the educational process. Supervision provides support to teachers in creating a conducive teaching-learning environment. This study identifies the roles of educational supervision, which include coordination, consultation, and evaluation. The process of implementing supervision is outlined in three stages: planning, implementation, and assessment.